The Role of Anung Suyatna's Leadership in The Management of The Panggalih Langgeng Art Studio in Kalianyar Village, Cirebon Regency - Dinda Retno Rosanti; Yohana Ari Ratnaningtyas; Arinta Agustina (Institut Seni Indonesia Yogyakarta, 2024)
Cirebon Regency boasts numerous art studios dedicated to promoting local culture. One such studio is Sanggar Langgeng Panggalih. This study investigates the leadership role of Anung Suyatna in managing Sanggar Langgeng Panggalih in Kalianyar Village, Cirebon Regency. Using a qualitative descriptive research method with a case study approach, the analysis uses George Terry's POAC (Planning, Organizing, Actuating, Controlling) management function theory and the situational leadership style of the Path-Goal approach theory developed by Robert House to understand the leadership style applied by Anung Suyatna in management of the Sanggar Langgeng Panggaalih studio. The results of the research show that the management system of Sanggar Langgeng Panggaalih involves members in the form of participation and freedom of opinion where studio members are involved in decision-making and the overall management process. It can be concluded that Anung Suyatna applies a participative leadership style. The achievement of management objectives is evident from the increasing offering of performances by Sanggar Langgeng Panggaalih and studio students are also starting to take part in many performance activities, especially the mask dance training program. This proves the effectiveness of Anung Suyatna's leadership style in achieving the management goals of Sanggar Langgeng Panggalih.